Deficiency in transmitter release triggers homeostatic transcriptional changes that increase presynaptic excitability - Caroline A. Cypranowska; Maya Feldthouse; Yoon Gi Choi; Dariya Bakshinska; Rachel Li; Zachary L. Newman; Ehud Y. Isacoff (Proceedings of the National Academy of Sciences, 2025)
Weakening of synaptic transmission at the Drosophila larval neuromuscular junction triggers two forms of homeostatic compensation, one that increases the probability of glutamate release per action potential ( P r ) and another that increases motoneuron (MN) activity. We investigated the molecular changes in MNs that underlie the increase in MN activity. RNA sequencing (RNA-seq) analysis on MNs whose glutamate release is weakened by knockdown of components of the MN transmitter release machinery reveals a reduction in expression of a group of genes that encode potassium channels and their positive modulators. These results identify a mechanism of compensation for weakened synaptic transmission by MNs, which engages a transcriptional program in those cells to increase firing and, thereby, ensure sufficient locomotory drive.